Influence of facial skin ageing characteristics on the perceived age in a Russian female population. (October 2015) - Merinville, E.; Grennan, G. Z.; Gillbro, J. M.; Mathieu, J.; Mavon, A.
Synopsis: Objective: The desire for a youthful look remains a powerful motivator in the purchase of cosmetics by women globally. To develop an anti‐ageing solution that targets the need of end consumers, it is critical to understand which signs of ageing really matter to them and which influence their age perception. To date, such research has not been performed in a Russian population. The aim of this work was to identify the signs of ageing that contribute the most to an 'older' or 'younger' look for Russian women aged 40 years old and above. Methods: The age of 203 Russian female volunteers was estimated from their standard photographs by a total of 629 female naïve assessors aged 20–65 years old. Perceived age data were related to 23 facial skin features previously measured using linear correlation coefficients. Differences in average severity of the correlating skin ageing features were evaluated between women perceived older and women perceived younger than their chronological age. Volunteers' responses to a ranking question on their key ageing skin concerns previously collected were analysed to provide an additional view on facial ageing from the consumer perspective. Results: Nine facial skin ageing features were found to correlate the most with perceived age out of the 23 measured. Such results showed the importance of wrinkles in the upper part of the face (crow's feet, glabellar, under eye and forehead wrinkles), but also wrinkles in the lower half of the face associated with facial sagging (upper lip, nasolabial fold). Sagging was confirmed of key importance to female volunteers aged 41–65 years old who were mostly concerned by the sagging of their jawline, ahead of under eye and crow's feet wrinkle. The severity of hyperpigmented spots, red and brown, was also found to contribute to perceived age although to a weaker extent. Conclusion: By providing a clear view on the signs of ageing really matter to Russian women who are aged 40 years old and above, this research offers key information for the development of relevant anti‐ageing solutions specifically targeting their needs and their desire to achieve younger‐looking skin.